2012
DOI: 10.1037/a0027843
|View full text |Cite
|
Sign up to set email alerts
|

An inconvenienced youth? Ageism and its potential intergenerational roots.

Abstract: Age is the only social category identifying subgroups that everyone may eventually join. Despite this, and despite the well-known growth of the older population, age-based prejudice remains an under-studied topic in social psychology. This paper systematically reviews the literature on ageism, highlighting extant research on its consequences and theoretical perspectives on its causes. We then identify a crucial gap in the literature: potential intergenerational tensions, speculating how a growing older populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
356
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(377 citation statements)
references
References 188 publications
(199 reference statements)
11
356
2
8
Order By: Relevance
“…However, most of these studies have been conducted among North Americans or Europeans, and there are few, if any, studies directly comparing attitude toward older adults across different cultures (Luo, Zhou, Jin, Newman, & Liang, 2013;Ng, 2002;North & Fiske, 2012, 2013aOta, Gallois, & Giles, 2002). Moreover, this existing body of literature presents inconsistent results regarding cultural differences in attitude toward older adults.…”
Section: Attitude Toward Older Adults: a Matter Of Cultural Value Or mentioning
confidence: 91%
“…However, most of these studies have been conducted among North Americans or Europeans, and there are few, if any, studies directly comparing attitude toward older adults across different cultures (Luo, Zhou, Jin, Newman, & Liang, 2013;Ng, 2002;North & Fiske, 2012, 2013aOta, Gallois, & Giles, 2002). Moreover, this existing body of literature presents inconsistent results regarding cultural differences in attitude toward older adults.…”
Section: Attitude Toward Older Adults: a Matter Of Cultural Value Or mentioning
confidence: 91%
“…While longer life expectancies are a positive outcome, the expanding older population may face challenges such as increased negative attitudes towards older people (Nelson, 2005; North & Fiske, 2012). In a US survey, nearly 80% of respondents aged 60 years or over reported having been discriminated against due to their age (Palmore, 2001), and a European survey found that ageism was the most commonly experienced type of discrimination, ahead of discrimination based on gender, ethnicity, disability, religion or sexual orientation (Abrams, Eilola, & Swift, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the prevalence of negative stereotypes about aging and elderly people (North & Fiske, 2012) identity conflict may often simply result in a generally lower level of identification with identities that are assumed to be typical for later life stages. For example, anecdotal evidence suggests that some youthful-looking baby boomers recoil at being called "grandma".…”
Section: Illustrating the Conflict Principle: Aging And Lifespan Of Imentioning
confidence: 99%